IMPLICATIONS OF DISCRETION IN THE HEAD OF LAND OFFICE IN LAND REGISTRATION - Upik Hamidah (Cepalo, 2019)
In certain circumstances, the minister of land and the head of the land office can register the scavenging of land rights in a parcel of land, which in this case the act was not done by the Land Deed Making Officer or PPAT. It is inversely proportional to the provisions contained in Article 37 paragraph (1) Government Regulation or PP No. 24 of 1997 concerning Land Registration which stipulates that the transfer of title to a parcel of land can only be done if it can be proven by a deed made by the authorized PPAT according to the provisions of the prevailing laws and regulations. The problem that will be discussed in this research is how the legal implications of the policy of the head of the land office in land registration? This study uses a normative legal method, with the approach to the legislation and other literature.   Based on the results of research that the policy of registering the transfer of ownership of a parcel of land carried out by the head of the land office is contrary to the provisions contained in Article 37 PP No. 24 of 1997 concerning Land Registration, so the transfer of rights to a parcel of land carried out is not legal according to law. The implication applies as long as the head of the land office explicitly registers the ownership rights to a parcel of land in an urban area, so it can be ascertained not to be categorised as a remote area as intended under Article 37 PP No. 24 of 1997. Thus, the content needs to be changed in Article 37 PP No. 24 of 1997, concerning regulation in certain circumstances. It would be better if the situation in question is specified in the torso so as not to cause multi-interpretation which can be a gap of abuse of authority so that it has the potential to harm the community.